2022
DOI: 10.3390/rs14030712
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Climate Change on Forest Fires in Yunnan Province, Southwest China Detected by GRACE Satellites

Abstract: Yunnan province in China has rich forest resources but high forest fire frequency. Therefore, a better understanding of the relationship between climate change and forest fires in this region is important for forest fire prevention. This study used the Gravity Recovery and Climate Experiment (GRACE) terrestrial water storage change (TWSC) data to analyze the influence of climate change on forest fires in the region during 2003–2016. To improve the accuracy and reliability of GRACE TWSC data, we used the genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Studies have also shown a negative correlation of summer rainfall in Southwest China with the simultaneous size and temperature of IO warm pool, and a positive correlation with that of the WP warm pool (Cao et al., 2014; Ueda et al., 2015). As the precipitation in rainy season prevents fire occurrence in Yunnan (Cui et al., 2022), it indicates that the cold phase of IO warm pool, regularly occurring in summer for the northern hemisphere, should promote the rainfall in Southwest China (Figure 2b). This may result from the enhancement of the land‐sea thermal contrast and the IO monsoon, corresponding to the rainy season in this region (Gu et al., 2020; Ha et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have also shown a negative correlation of summer rainfall in Southwest China with the simultaneous size and temperature of IO warm pool, and a positive correlation with that of the WP warm pool (Cao et al., 2014; Ueda et al., 2015). As the precipitation in rainy season prevents fire occurrence in Yunnan (Cui et al., 2022), it indicates that the cold phase of IO warm pool, regularly occurring in summer for the northern hemisphere, should promote the rainfall in Southwest China (Figure 2b). This may result from the enhancement of the land‐sea thermal contrast and the IO monsoon, corresponding to the rainy season in this region (Gu et al., 2020; Ha et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Each record with the time and location of wildfire were used here, and 5,483 records in 18 years were collected. Undeniably, most ignition sources of wildfire were from human activities, but wildfire occurrence must dominantly be attributed to the air moisture and other climatic conditions in Yunnan (Cui et al., 2022; Ying et al., 2021). Obviously characterized by climatic conditions, with about 99% of the total fire number in winter and spring, there are indeed distinction on wildfire number between the locally practical fire alarming season (winter and spring, or December‐May) and nonfire alarming season (summer and autumn, or June‐November) across Yunnan (Figures 2a and 2b).…”
Section: Methodsmentioning
confidence: 99%
“…According to the relative covariance of different observation series by using the GCTH method, the different datasets were fused by taking a weighted average of them [ 36 ]. where and are the th observation time series and its corresponding weight, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…According to the relative covariance of different datasets obtained by using the GTCH method, we fused the different datasets by taking a weighted average of them [45].…”
Section: Data Fusionmentioning
confidence: 99%